The Effect of Organic Fertilizer to The Growth and Yield of Soybean (Glycine max L. Merrill) Cultivated on Post Coal Minning Soil - dwi eky (Mulawarman University, 2018)
This research aimed to determine the effect of organic fertilizer to the growth and yield of soybean cultivated on post coal minning soil. The experiment was conducted in Loa Bahu Village, Sungai Kunjang District. The design of the experiment used Completely Randomized Design (CRD) with 8 replications. The treatment is dossage of organic fertilizer (chicken manure bokhasi), consisted of five level. ie: P0 (control, without fertilizer), P1 (17.5 g polybag-1), P2 (35 g polybag-1), P3 (52.5 g polybag-1), and P4 (70 g polybag-1). Data were analyzed using analysis of variance, followed by DMRT at 5% level. The results showed that organic fertilizer was significantly influence the height of the plants at 45 days after planting (DAP), number of seeds per plant, weight of 100 seeds, harvesting time, and total biomass weight. On the other hand it has no significant effect on plant height at 15 DAP, 30 DAP and at harvest time, as well as flowering time, number of branches per plant, number of pods per plant, number of seeds per pod, and weight of seeds per plant. There was a significant different effect of post coal minning soil applied with and without organic fertilizer to the growth and yield of soybean. In addition there was no significant different effect among the organic fertilizer dosage applied. The lowest organic fertilizer dosage of 17,5 g polybag-1 (P1) was considered as the best treatment in this study, since it gave the highest yield per plant. We observed a dominant vegetative growth of soybean, noticed from plant height which was twice higher, and flowering as well as harvesting time which was more than a month longer from general description of soybean variety Anjasmoro. It was suggested that fertility and acidity status (pH 7,43) of the post coal minning soil causing that condition.